ENGLISH EDUCATION GRADUATES CONFRONT ENGINEERING CHALLENGES IN POSTMODERN ENGLISH FOR SPECIFIC PURPOSES ERA - Muryani, Rera Nadian (International Journal of Instructions and Language Studies, 2026)
In the postmodern era marked by interdisciplinarity and rapid technological advancement, English for Specific Purposes (ESP) instruction in engineering contexts demands both linguistic competence and disciplinary awareness. English Education graduates appointed as ESP instructors in engineering faculties often face tensions arising from the gap between their pedagogical training and specialized technical knowledge. This qualitative study employs a narrative inquiry approach to explore the lived experiences, professional identity negotiation, and adaptive strategies of an English Education graduate teaching engineering-focused ESP at a private university in Pasuruan, East Java, Indonesia. Data were collected through semi-structured interviews and reflective documentation and analyzed using thematic analysis. The findings reveal three major themes: (1) an epistemic gap between linguistic expertise and engineering content knowledge, particularly in understanding technical terminology and genre conventions; (2) ongoing negotiation of professional identity and epistemic authority within interdisciplinary classrooms where students may possess stronger technical backgrounds; and (3) adaptive strategies and continuous professional development, including self-directed learning, use of authentic engineering materials, collaboration with engineering colleagues, and implementation of genre-based and task-oriented pedagogy. The study indicates that these challenges stem not from individual inadequacy but from structural separation between language education and technical disciplines in higher education. It further highlights a shift in teacher authority from content mastery to communicative mediation, positioning ESP instructors as facilitators who bridge language and disciplinary discourse. The findings suggest the need for greater interdisciplinary integration in teacher education programs to better prepare graduates for specialized academic contexts.